Review of tennis serve motion analysis and the biomechanics of three serve types with implications for injury - Abrams, G. D.; Sheets, A. L.; Andriacchi, T. P.; Safran, M. R. (Sports Biomechanics, 2011)
The tennis serve has the potential for musculoskeletal injury as it is an overhead motion and is performed repetitively during play. Early studies evaluating the biomechanics and injury potential of the tennis serve utilized skin-based marker technologies; however, markerless motion measurement systems have recently become available and have obviated some of the problems associated with the marker-based technology. The late cocking and early acceleration phases of the kinetic chain of the service motion produce the highest internal forces and pose the greatest risk of injury during the service motion. Previous biomechanical data on the tennis serve have primarily focused on the flat serve, with some data on the kick serve, and very little published data elucidating the biomechanics of the slice serve. This review discusses the injury potential of the tennis serve with respect to the four phases of the service motion, the history, and early findings of service motion evaluation, as well as biomechanical data detailing the differences between the three types of serves and how this may relate to injury prevention, rehabilitation, and return to play.